Epigenetic Regulation of Nucleotide Excision Repair - Li, Wentao; Jones, Kyle; Burke, Tyler J.; Hossain, Md Akram; Lariscy, Leah (Frontiers in Cell and Developmental Biology, 2022)
Genomic DNA is constantly attacked by a plethora of DNA damaging agents both from endogenous and exogenous sources. Nucleotide excision repair (NER) is the most versatile repair pathway that recognizes and removes a wide range of bulky and/or helix-distorting DNA lesions. Even though the molecular mechanism of NER is well studied through in vitro system, the NER process inside the cell is more complicated because the genomic DNA in eucaryotes is tightly packaged into chromosomes and compacted into a nucleus. Epigenetic modifications regulate gene activity and expression without changing the DNA sequence. The dynamics of epigenetic regulation play a crucial role during the in vivo NER process. In this review, we summarize recent advances in our understanding of the epigenetic regulation of NER.